The meaning of administrative tools to the administrative processes in the public sector - Porota, Barbara Dudu (University of the Free State, 1997)
Abstract not available
Keywords: Public administration; Legislative body; Public institutions; Administrative tools; Information system; Dissertation (M.P.A. (Public Administration))--University of the Free State, 1997